States of Inquiry Social Investigations and Print Culture in Nineteenth-Century Britain and the United States - Frankel, Oz (Johns Hopkins University Press, 2006)
In the mid-nineteenth century, American and British governments marched with great fanfare into the marketplace of knowledge and publishing. British royal commissions of inquiry, inspectorates, and parliamentary committees conducted famous social inquiries into child labor, poverty, housing, and factories. The American federal government studied Indian tribes, explored the West, and investigated the condition of the South during and after the Civil War.Performing, printing, and then circulating these studies, government established an economy of exchange with its diverse constituencies. In this medium, which Frankel terms "print statism," not only tangible objects such as reports and books but knowledge itself changed hands. As participants, citizens assumed the standing of informants and readers. Even as policy investigations and official reportage became a distinctive feature of the modern governing process, buttressing the claim of the state to represent its populace, government discovered an unintended consequence: it could exercise only limited control over the process of inquiry, the behavior of its emissaries as investigators or authors, and the fate of official reports once issued and widely circulated.This study contributes to current debates over knowledge, print culture, and the growth of the state as well as the nature and history of the "public sphere." It interweaves innovative, theoretical discussions into meticulous, historical analysis.